Incidência de defeitos dentinários e fratura vertical da raiz após retratamento endodôntico e ciclagem mecânica - Bello, Mariana De Carlo (2013)
The aim of this study was to evaluate the incidence of dentin defects and Vertical Root Fractures (VRF) after endodontic retreatment and mechanical cycling. Methods: Two hundred monorradiculars premolars were divided into five groups. Forty teeth were left unprepared (control group). The other teeth were prepared with ProTaper files up to size F3 and filled with gutta percha and AH Plus. Eighty teeth were filled with the lateral compaction technique (LCT) and eighty teeth were filled with single cone technique (SCT). The filling material of forty teeth of each group was removed with ProTaper retreatment files and the canal was re-prepared with ProTaper files up to size F5 and filled with LCT (LCTR group) and SCT (SCTR group). All teeth were subjected to mechanical cycling (1.000,000 cycles, 130 N, 2.2 Hz and 37°C). The roots were sectioned horizontally at 3, 6 and 9 mm from the apex and observed under a 20X stereomicroscope. The defects were classified as: no defect‟, Vertical Root Fracture‟ and other defects‟. The difference between the group was analyzed using the Fisher‟s exact and Chi-squared tests. Results: The mechanical cycling alone did not promote dentin defects and VRF. The experimental groups presented higher dentin defects than the control group (P = 0.021). Retreatment groups did not present higher amounts of dentin defects that groups subjected to first treatment (P > 0.05). VRF was observed only in the SCTR group. Conclusion: Endodontic treatment and retreatment procedures that induce little dentin defects. The filling techniques do not seem to affect regarding the number of dentin defects in human premolars.